General trait and workplace fear of missing out (FoMO) and the neurodiverse mind: Exploring autism, ADHD, and internal representation profiles - McKee, Paul; Boulhadi, Khaoula; Nadelhoffer, Thomas (Personality and Individual Differences, 2026)
Keywords: Mental representation; Psychometrics; Representation (politics); Social perception; Trait; dept.psy

Thinking differently: neurodivergent traits and responses to thought experiments in philosophers and the general population - McKee, Paul; Boulhadi, Khaoula; Weymouth, Helena; Nadelhoffer, Thomas (Philosophical Psychology, 2026)
Philosophers have long speculated that individual differences in temperament influence philosophical thinking, yet empirical research has rarely explored the role of neurodivergent traits in this domain. In this large online study (N = 1,254), we investigated whether participants with training in philosophy differ from the general population when it comes to six psychological traits–autism, ADHD, aphantasia, anendophasia, anauralia, and representational manipulation–and also whether these traits correlate with responses to two widely studied philosophical thought experiments: the “trolley problem” and the “rollback deterministic universe.” Compared to the general population, participants with training in philosophy had higher scores on measures of ADHD, internal verbalization, and representational manipulation, but lower scores on measures of visual imagery. These cognitive traits were also correlated with participants’ moral and metaphysical judgments (independent of their level of philosophical training)–e.g. participants who scored higher in visualization were less likely to judge that hitting the switch in the trolley problem is permissible but not obligatory, and also less likely to attribute free will and moral responsibility to agents in the rollback universe. Finally, we employed machine learning to develop predictive models that classify a randomly selected participant as either a philosopher or a non-philosopher. Models trained solely on responses to measures for neurodivergent traits achieved better performance than models trained solely on responses to philosophical thought experiments. This suggests that stable, trait-level neurodivergent characteristics may be more diagnostic of philosophical interest, aptitude, or training than judgments philosophers make on domain-relevant problems. © 2026 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Neurodiversity; dept.psy; experimental philosophy; free will beliefs; general population; moral judgment; philosophers